2017
DOI: 10.1371/journal.pone.0169830
|View full text |Cite
|
Sign up to set email alerts
|

Anti-rheumatic treatment is not associated with reduction of pentraxin 3 in rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis

Abstract: BackgroundPentraxin 3 is proposed to be a marker of inflammation and cardiovascular risk, but its role in inflammatory rheumatic diseases (IRDs) is still uncertain. Therefore, we wanted to examine if anti-rheumatic treatment reduced serum PTX3 (s-PTX3) levels in IRDs, and if s-PTX3 levels were related to other markers of inflammation and to endothelial function (EF).MethodsWe examined s-PTX3, EF and established inflammatory biomarkers in 114 IRD patients from the PSARA study before and after 6 weeks and 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
2
15
2
Order By: Relevance
“…However, the PTX3 levels were mainly affected by active vasculitis, but not the prednisolone dose [ 20 ]. In addition, methotrexate seems not to affect PTX3 level in TAK, and it was proved not to influence PTX3 in inflammatory rheumatic disease [ 12 , 33 ]. However anti-IL-6 showed contrary results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the PTX3 levels were mainly affected by active vasculitis, but not the prednisolone dose [ 20 ]. In addition, methotrexate seems not to affect PTX3 level in TAK, and it was proved not to influence PTX3 in inflammatory rheumatic disease [ 12 , 33 ]. However anti-IL-6 showed contrary results.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous article based on the same patient sample demonstrated that MTX and anti-TNF ± MTX treatment significantly reduced inflammatory activity (determined by ESR, CRP, WBC count, PGA, and PtGA) both at 6 weeks and at 6 months compared to baseline [ 16 ]. This may indicate that both treatment regimens have a longstanding effect on inflammation, but only MTX (in patients potentially responding to it) has a prolonged beneficial effect on the endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in PSARA, an observational study, had been included at the Lillehammer Hospital for Rheumatic Diseases as described elsewhere [ 16 ]. Briefly, the inclusion criteria were: males and females with an age range 18–80 years; and PsA according to the Moll and Wright 1973 criteria [ 17 ], AS according to the modified New York diagnostic criteria for AS [ 18 ], or RA according to the ACR 1987 criteria [ 19 ], and clinical indication for starting with either MTX monotherapy or anti-TNF treatment with or without MTX comedication (anti-TNF ± MTX).…”
Section: Methodsmentioning
confidence: 99%
“…This observational prospective study is based on all SpA patients (31 PsA, and 20 AS) who completed 6 months follow-up in the PSARA (PSoriatic arthritis, Ankylosing spondylitis, Rheumatoid Arthritis) study, described in detail elsewhere [17]. Patients were recruited from October 2008 to May 2010.…”
Section: Methodsmentioning
confidence: 99%